Association Between Lumbar Vertebral MRI Findings and Neuropathic Pain in Patients With Low Back Pain at Prof. Dr. Margono Soekarjo General Hospital - Hening Yanita Rizki Adiputri; Prasetyo Tri Kuncoro; Untung Gunarto; Tisna Sendy Pratama; Octavia Permatasari; Kamal Agung Wijayana; Muhamad Rifqy Setyanto (Medical and Health Journal, 2026)
Background: Low back pain (LBP) is a common musculoskeletal condition that may be accompanied by neuropathic pain due to irritation or compression of lumbar neural structures, often associated with structural abnormalities detected on MRI. Objective: This study aimed to assess the association between lumbar MRI findings and neuropathic pain in patients with LBP at Prof. Dr. Margono Soekarjo General Hospital. Methods: An analytical observational study with a cross-sectional design was conducted involving 68 patients, using lumbar MRI data and neuropathic pain screening with the ID Pain questionnaire. Associations were analyzed using Chi-square tests and multivariate logistic regression with a significance level of p < 0.05. Results: The most frequent MRI findings are herniated nucleus pulposus (85.3%), spinal stenosis (57.4%), spondylosis (38.2%), and spondylolisthesis (19.1%), while neuropathic pain is identified in 66.2% of patients. Significant associations are observed between neuropathic pain and all MRI findings, with lumbar spinal stenosis identified as the strongest predictor. Conclusion: Lumbar MRI abnormalities are significantly associated with neuropathic pain in patients with LBP, and spinal stenosis represents the most influential factor, emphasizing the importance of radiological evaluation in the management of LBP with neuropathic components.